The Effect of Corporate Governance on Firm Value in Food and Beverage Sector Companies in Indonesia - Purwanti, Titik; Kuntaryanto, Oki; Utami, Tri; Marjukah, Anis; Darmawansyah, Iwan; Kalbuana, Nawang (Universitas Nahdlatul Ulama Sidoarjo, 2024)
This study examines the effect of corporate governance through institutional ownership, public ownership, and audit committee on firm value in the food and beverage sector listed on the Indonesia Stock Exchange (IDX). The research sample consisted of 32 companies from a total of 49 companies listed in the 2020-2022 period, which were selected using purposive sampling method based on certain criteria. The analysis was carried out using multiple linear regression, the results showed that the three variables had a significant effect on firm value as measured by the Price to Book Value (PBV) ratio. Institutional ownership shows the strongest influence, which shows the importance of external supervision in improving the efficiency and transparency of the company. Public ownership, despite its smaller effect, still contributes to management accountability and stock liquidity. The existence of an effective audit committee also plays an important role in improving the integrity of financial statements and risk management, which in turn increases investor confidence and firm value. This study confirms the importance of good corporate governance to increase the market value of companies in the food and beverage sector.